Dieta y salud en época Clásica - García-González, José Antonio (Universidad de Málaga. Facultad de Filosofía y Letras, 2010)
La dietética constituía una de las principales bases de la medicina griega, tanto a nivel explicativo como terapéutico. El concepto de dieta hay que entenderlo no sólo como un régimen alimenticio, sino más bien como el modo de vida y la propia realidad del individuo en toda su complejidad.

The dietetics constituted one of the principal bases of the Greek medicine, both at explanatory and therapeutic level. The concept of diet is necessary to understand it not only as a nutritive regime, but rather as the way of life and the proper reality of the individual in all his complexity.
Keywords: Dietética; Corpus Hippocraticum; S. V a.C.; Medicina griega; Salud; Dieta; 5th century B.C.; Greek medicine; Health; Diet